The safety of introducing a new generation TAVR device: one departments experience from introducing a second generation repositionable TAVR. Issue 1 (December 2017) - Bjursten, Henrik; Nozohoor, Shahab; Johansson, Malin; Zindovic, Igor; Appel, Carl-Fredrik; Sjögren, Johan; Dencker, Magnus; Olivecrona, Göran; Harnek, Jan; Koul, Sasha; Feldman, Ted; Reardon, Michael; et al.
Abstract Background In the evolving field of transcatheter aortic valve replacements a new generation of valves have been introduced to clinical practice. With the complexity of the TAVR procedure and the unique aspects of each TAVR device, there is a perceived risk that changing or adding a new valve in a department could lead to a worse outcome for patients, especially during the learning phase. The objective was to study the safety aspect of introducing a second generation repositionable transcatheter valve (Boston Scientific Lotus valve besides Edwards Sapien valve) in a department. Methods In a retrospective study, 53 patients receiving the Lotus system, and 47 patients receiving the Sapien system over a period of three years were compared for short-term outcome according to VARC-2 definitions and 1-year survival. Results Outcome in terms VARC-2 criteria for early safety and clinical efficacy, stroke rate, and survival at 30 days and at 1 year were similar. The Lotus valve had less paravalvular leakage, where 90% had none or trace aortic insufficiency as compared to only 48% for the Sapien system. Conclusions Introduction of a new generation valve can be done with early device success and safety, and without jeopardizing the outcome for patients up to one year. We found no adverse effects by changing valve type and observed improved outcome in terms of lower PVL-rates. Both existing and new centers starting a TAVR program can benefit from the use of a new generation device.